El resurgir de viejos fantasmas: política asistencial y mundo del trabajo = The resurgence of old ghosts: social assistance policy and labor world - Ribero, Ximena Baráibar (Textos & Contextos (Porto Alegre))
Since the end of the nineties, Latin America has widened and institutionalized its social assistance policies, mainly by the implementation of Conditional Cash Transfer Programs. In Uruguay, these programs have been implemented since 2005. One of the more debatable topics regarding these programs has been their impact on work and whether transfer programs would not incentive beneficiaries to work and promote their dependency with the State. This paper presents the Uruguayan case analyzing Conditional Cash Transfer Programs and the world of work stating there is no such impact of these programs on adult work. Rather, these concerns are old ghosts which have always been present in the social assistance arena